NILAI PENDIDIKAN KARAKTER DALAM CERITA AWANG MAHMUDA VERSI RAMLI USMAN - Fitriani, Resty Anindita; Syafrial, Syafrial; Rumadi, Hadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACT: This study discusses character education anything contained in the story of Usman Awang Ramli Mahmuda version? This study aimed to describe eany character education contained in the story of Usman Awang Ramli Mahmuda version. Sources of data in this study is the story of Usman Awang Ramli Mahmuda version. The method used in this research is descriptive analisis.Teknik data collection in this study using the technique of character education documentation contained in the story of Usman Awang Ramli Mahmuda version. Character education values in clude: (1) 28 Religious Data, (2) honest 5 flat, (3), self-2 data, (4) 3 disciplines of data, (5) the responsibility of 8 data, (6) tolerance 2 the data, (7) workhard 2 data, (8) the data concerned social 5, (9) 5 pacifist of data, (10) creative 2 data. Educational value of the most dominant character is the value of a religious character educationKeywords: character education, Awang Mahmuda story